High maternal-fetal HLA eplet compatibility is associated with severe manifestation of preeclampsia - Stefańska, Katarzyna; Kurkowiak, Małgorzata; Piekarska, Karolina; Chruściel, Elżbieta; Zamkowska, Dorota; Jassem-Bobowicz, Joanna; Adamski, Przemysław; Świątkowska-Stodulska, Renata; Abacjew-Chmyłko, Anna; Leszczyńska, Katarzyna; Zieliński, Maciej; Preis, Krzysztof; et al. (Frontiers in Immunology, 2023)
Gestational hypertension is the most common cause of maternal and fetal morbidity and mortality, but its pathogenesis is poorly understood. As pregnancy resembles allograft transplantation, we hypothesized that maternal-fetal HLA incompatibility may be involved in pathogenesis of gestational hypertension and its progression to preeclampsia. HLA class I and class II antigens were typed with next generation sequencing in 61 women and their children. Then, maternal-fetal HLA eplet mismatch load was determined with in silico approach HLAMatchmaker algorithm. High HLA-C, -B and DQB1 maternal-fetal eplet compatibility was associated with severe PE manifestation. Both quantity and quality of HLA eplet mismatches affected severity of PE. Mismatches in HLA-B eplets: 65QIA+76ESN, 70IAO, 180E, HLA-C eplets: 193PL3, 267QE and HLA-DRB1 eplet: 16Y were associated with mild outcome of PE if occurred. HLAincompatibility between mother and an offspring is crucial for induction of tolerance to semiallogenic fetus and required for physiological outcome of pregnancy.